Determinan Penerimaan Opini Audit Going Concern pada Perusahaan Property dan Real Estate - Sari, Sisca Yuridiska; Rahmatika, Dien Noviany (Universitas Swadaya Gunung Jati, 2017)
AbstractThe purposes of this research are to examine the influence of tenure audit, opinion shopping and auditor reputation on acceptance of going concern audit opinion. This research was done to the sub sectors and property company in 2013-2015. The data which is used this secondary data by using purposive sampling technique. Analysis technique which is used in this research is descriptive with quantitative approach using descriptive statistical test, multicolinearity test, logistic regression analysis, and coefficient of determination. The result shows that audit of tenure, opinion shopping, and auditor reputation simultaneously affect the acceptance of going concern audit opinion, audit tenure does not affect the acceptance of going concern audit opinion, opinion shopping does not affect the acceptance of going concern audit opinion, auditor reputation has an effect on acceptance of going concern audit opinion.Keywords: Acceptance of going concern audit opinion; Audit tenure; Auditor reputation; Opinion shopping.AbstrakPenelitian ini bertujuan untuk menguji pengaruh audit tenure, opinion shopping dan reputasi auditor terhadap penerimaan opini audit going concern. Penelitian ini dilakukan pada perusahaan sub sektor property dan real estate tahun 2013-2015. Data yang digunakan pada penelitian ini adalah data sekunder dengan pengambilan sampel menggunakan purposive sampling. Teknik analisis data yang digunakan adalah teknik deskriptif dengan pendekatan kuantitatif menggunakan uji statistik deskriptif,uji kelayakan model regresi, uji multikolinearitas, analisis regresi logistik, dan koefisien determinasi. Hasil yang peroleh menunjukkan bahwa audit tenure, opinion shopping, dan reputasi auditor secara simultan berpengaruh terhadap penerimaan opini audit going concern, audit tenure tidak berpengaruh terhadap penerimaan opini audit going concern, opinion shopping tidak berpengaruh terhadap penerimaan opini audit going concern, dan reputasi auditor berpengaruh terhadap penerimaan opiniaudit going concern.Kata kunci: Audit tenure; Opinion shopping; Penerimaan opini audit going concern; Reputasi auditor.